2001
DOI: 10.1023/a:1005256122649
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A total of 52 patients with Parkinson's disease (PD), 11 with presumptive Alzheimer's disease (AD), and 20 healthy subjects were studied; subjects were aged 55-74 years. Neurological symptoms were assessed quantitatively, and the state of higher mental processes were evaluated using the Luriya method. A number of memory tests were also used. These studies showed that PD was almost always accompanied by memory impairment exceeding the age norm. The major mechanism for memory impairment in PD without dementia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…This variance may represent differences in the definition of MCI (statistical cut-offs vs. clinical determination of impairment), measurements used, and/or population characteristics. On the other hand, some previous studies of early cognitive dysfunction in PD have documented similar high rates of memory dysfunction [27]. The fact that in our study memory disturbance was largely accompanied by executive dysfunction may suggest that PD memory impairment is secondary to executive difficulties.…”
Section: Discussioncontrasting
confidence: 42%
“…This variance may represent differences in the definition of MCI (statistical cut-offs vs. clinical determination of impairment), measurements used, and/or population characteristics. On the other hand, some previous studies of early cognitive dysfunction in PD have documented similar high rates of memory dysfunction [27]. The fact that in our study memory disturbance was largely accompanied by executive dysfunction may suggest that PD memory impairment is secondary to executive difficulties.…”
Section: Discussioncontrasting
confidence: 42%
“…Studies indicate AD caregiving relationships are stressful (Martire, Lustig, Schulz, Miller & Helgeson, 2004; McClendon, Smyth & Neundorfer, 2004; Schulz & Martire, 2004; Quinn, Clare & Woods, 2009; Vitaliano, Zhang, & Scanlan, 2003). Parkinson’s disease (PD), exemplified by both progressive movement disorders as well as non-motor neuropsychiatric symptoms, afflicts more than 1.5 million older adults United States (Van Den Eeden, Tanner, Bernstein, Robin, & Fross, 2003) and places unique demands on informal caregivers to cope with complex medication regimens, increasing mobility limitations and, for 20% or more of PD care recipients, profound cognitive loss as well (Zakharov, Akhutina & Yakhno, 2001). An increasing number of PD study reports indicate that PD caregivers are particularly stressed by caregiving (Aarsland, Larsen, Karlsen, Lim & Tandberg, 1999; Hooker, Manoogian-O’Dell, Monahan, Frazier, & Shifren, 2000; Roland, Jenkins & Johnson, 2009; Lyons, Stewart, Archbold, & Carter, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has shown temporal order memory to be impaired in PD (Dubois & Pillon, 1997; Sagar et al, 1988; Taylor et al, 1986; Zakharov et al, 2001), this is the first study, to the authors’ knowledge, to examine the effect of interference on temporal order memory in PD. The findings provide novel insight into a processing deficit that may have an impact on multiple cognitive functions and the execution of various daily living skills in individuals with PD.…”
Section: Discussionmentioning
confidence: 84%
“…Evidence from previous studies indicates that temporal order memory is impaired in individuals with PD (Dubois & Pillon, 1997; Sagar et al, 1988; Taylor et al, 1986; Zakharov et al, 2001). Zakharov and colleagues (2001) found that individuals with PD were impaired on the sequential ordering portion of a memory test.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation